Cognitive trajectories in relation to hospitalization among older Swedish adults. (January 2018) - Hallgren, Jenny; Fransson, Eleonor I.; Reynolds, Chandra A.; Finkel, Deborah; Pedersen, Nancy L.; Dahl Aslan, Anna K.
Highlights: For persons being hospitalized the main decline occurs before the hospitalization. Persons being hospitalized exhibited a lower mean level of cognitive performance. Not hospitalized persons experienced steeper decline in cognition after age of 70. Future research on factors affecting cognitive change prehospitalization are needed. Abstract: Introduction: Research indicate that cognitive impairment might be related to hospitalization, but little is known about these effects over time. Objective: To assess cognitive change before and after hospitalization among older adults in a population-based longitudinal study with up to 25 years of follow-up. Method: A longitudinal study on 828 community living men and women aged 50–86 from the Swedish Adoption/Twin Study of Ageing (SATSA) were linked to The Swedish National Inpatient Register. Up to 8 assessments of cognitive performance (general cognitive ability, verbal, spatial/fluid, memory, and processing speed) from 1986 to 2010 were available. Latent growth curve modelling was used to assess the association between cognitive performance and hospitalization including spline models to analyse cognitive trajectories pre- and post-hospitalization. Results: A total of 735 persons (89%) had at least one hospital admission during the follow-up. Mean age at first hospitalization was 70.2 (±9.3) years. Persons who were hospitalized exhibited a lower mean level of cognitive performance in general ability, processing speed and spatial/fluid ability compared with those who were not hospitalized. The two-slope models revealed steeper cognitive decline before hospitalization than after among those with at least one hospitalization event, as compared to non-hospitalized persons who showed steeper cognitive decline after the centering age of 70 years. Conclusions: Persons being hospitalized in late life have lower cognitive performance across all assessed domains. The results indicate that the main decline occurs before the hospitalization, and not after. This might indicate that when you get treatment you also benefit cognitively.